Surface NMR for hydrogeology : a user's guide - Legchenko, Anatoly (IOP (Series). Release 21., 2021)
Surface nuclear magnetic resonance (SNMR) is a newly developed, non-invasive geophysical method designed for groundwater prospecting. This book provides an overview of the SNMR method and a cost-benefit analysis of SNMR against other geophysical methods applied to groundwater study. It assesses the methodology of field measurements and gives examples of real data interpretation, and deals with some of the most pervasive problems faced by the SNMR methodology. Based on the author's extensive teaching experience, this book is designed to acquaint a wide but specialist audience of researchers and professionals in hydrogeology and geophysics with the SNMR method.